Mobility in a Post-Pandemic City: Subjective Considerations Based on Observations and âThe Plagueâ by Albert Camus - Jacek SzoÅtysek (Journal of Regional and City Planning, 2020)
The functioning of the city during a pandemic under the influence of social isolation forced by the state authorities and the suspension of a significant part of economic activity forced by administrative decisions causes changes in the minds of the city's inhabitants. This will highly likely translate into a new image of the city in the post-pandemic period. The aim of this article is to review the antecedents of the functioning of the post-pandemic city and to outline the premises of probable changes in the mobility of the inhabitants of the post-pandemic city. The aim is to point out the changes that occur as a result of responding to the pandemic in sudden reaction mode, which are likely to occur again in the future and are related to the consequences described inductively as the following sequence: inhabitants' emotions"”changes in behaviour"”organisational, political and social changes"”infrastructural changes"”potential impact on inhabitants and functioning of the city. The awareness of the possibility of such changes is important for all those whose professional and personal lives are connected with cities, as anticipating changes allows for proactive reactions, reducing possible failures. Since we, mankind in the 21st century, consider ourselves a species that is reasonable and teachable with respect to its own mistakes, I recognize in these considerations the context of an epidemic such as described by Albert Camus in his novel The Plague, indicating that we have not learned from what we experienced almost 100 years ago with the Spanish flu.Abstrak. Berfungsinya kota-kota selama pandemi dalam pengaruh isolasi sosial yang diterapkan oleh pemerintah dan penangguhan sebagain besar aktifitas ekonomi oleh keputusan administratif menyebabkan perubahan pemikiran penduduk kota. Keadaan ini akan sangat mungkin diartikan sebagai citra baru kota di periode pasca-pandemi. Tujuan dari artikel ini adalah untuk mengulas fungsi kota pasca-pandemi yang lampau dan untuk menguraikan hal-hal yang mungkin berubah pada mobilitas penduduk kota pasca-pandemi. Ini untuk menunjukkan perubahan yang terjadi sebagai akibat reaksi secara mendadak terhadap pandemi yang mungkin terjadi di masa depan, dan terkait dengan konsekuensi yang digambarkan secara induktif sebagai sebuah urutan: emosi penghuni "“ perubahan perilaku "“ perubahan organisasi, politik dan sosial "“ perubahan infrastruktur "“ dampak potensial terhadap penduduk dan fungsi kota. Kesadaran akan kemungkinan perubahan tersebut penting bagi semua orang yang kehidupan profesional dan pribadinya terhubung dengan kota, karena mengantisipasi perubahan memungkinkan reaksi proaktif yang dapat mengurangi kemungkinan kegagalan. Sebagai umat manusia abad ke-21, yang menganggap diri kita spesies yang berakal dan dapat belajar atas kesalahannya sendiri, penulis menengarai dalam konteks wabah, sebagaimana dikatakan oleh Albert Camus dalam novel The Plague, kita belum belajar dari apa yang kita alami dengan Spanish flu hampir 100 tahun yang lalu.Kata kunci. kota pasca pandemi, mobilitas, epidemi, kualitas hidup, ruang publik.